Greek Medicine from Hippocrates to Galen : Selected Papers - Jouanna, Jacques (2012)
This volume makes available in English translation a selection of Jacques Jouanna's papers on Greek and Roman medicine, ranging from the early beginnings of Greek medicine to late antiquity...